PENGARUH TEMPERATUR TERHADAP PEMBENTUKAN KERAK GIPSUM DALAM PIPA - Sutrisno Sutrisno; S. Muryanto S. Muryanto; AP Bayuseno (Gema Teknologi, 2012)
Sutrisno, S. Muryanto, AP Bayuseno, in this paper explain that gypsum crust (CaSO4.2H2O) that occurs in the pipe very detrimental to the industry because it resulted in narrowing of the cross-section, reinforcing walls, inhibit heat transfer and slow processing time. Therefore, gypsum crust should be prevented or inhibited growth. Gypsum crust growth is affected by the concentration, temperature and flow rate as well as impurities. This study aimed to determine the effect of temperature on the formation of gypsum crust. Gypsum scaling experiments carried out by reacting a NaSO4 with CaCl2 in a test tool that has been designed. The experiments were performed at a temperature of 27oC-50oC with Ca2 + concentration of 3500 ppm, flow rate 30 ml / min and stainless steel test pipes. Results from this study showed a rise in temperature by lowering the induction time and increase mass scale and make a longer crystal sizes. Test results morphology, composition and purity of the results of the experiment showed that the crust was beanr gypsum. Keywords : gypsum, scale, temperature